The effect of sports-metrics volleyball training on the landing error scoring system in female volleyball players - shahnaz shahrjerdi; Heman Mohammadi; sharareh Amiri (Sport Sciences and Health Research)
Background: Excessive repetitions of the landing and jumping task are a key risk factor for lower extremity injury (specially ACL) in female volleyball players.Aim: this study investigates the effect of Sports-Metrics Volleyball Training (SMVT) on landing technique in female volleyball players.Materials and Methods: The participants of this study were 25 female young volleyball players and randomly divided into training (TG, n=13) and control groups (CG, n=12). The TG performed SMVT for 18 sessions, and the CG performed their regular training. Landing error scoring system (LESS) test were used for assessing landing errors. SPSS (version 25) was used to analyze the statistical data (P<0.05).Results: The results of the data analysis showed a significant improvement (P=0.01) in LESS in TG (from 8.62 to 5.54), but no significant changes in CG the LESS (P=0.62, from 8.00 to 8.23). Eighteen sessions SMVT reduced the landing error by 35.73% in the TG.Conclusion: Base on previous research the SMVT reduces lower extremity injuries and the results of this study showed that SMVT significant improvement the landing technique. Therefore, performing SMVT is recommended for female volleyball players because it is effective in both preventing injuries and improving landing technique.